Salivary flow and corono-radicular caries in elderly patients - Campodónico Reategui, Carlos (2012)
The aim of this study was to determine the correlation between hypo-salivation and corono-radicular caries in older adult patients, which analyzed the physicochemical properties of saliva (flow, pH), the frequency and location of the corono-radicular caries. Was selected a sample of 45 persons, adult patients over 60 years and another 18 to 26 years (control group), from service centers, hospitals and universities. The technique of collection of saliva, consisted of making chewing a piece of paraffin for a period of five minutes and gradually spit in a tank, which allowed to measure the volume and pH salival. We observed the oral higiene and the corono-radicular caries of all tooth surfaces. The results, the volume of saliva in the elderly, had an average of 3.27 ml/5min very low values compared with the values of young people who have an average of 5.22 ml/5min. It was found that 98 % of seniors showed poor oral hygienes. On crown-root caries, the average mouth of teeth present in older adults was 16 pieces, but these pieces by 95 % were affected by decay with a mean of 5.8 and ±3.8. On the relationship between hyposalivation and dental caries, could not be determined, since the plaque was very high at 98 %, it was observed that older adults are at high risk of corono-radicular caries. To avoid this severe pathology is necessary to intervene in that age group.